2016
DOI: 10.1144/sp423.12
|View full text |Cite
|
Sign up to set email alerts
|

Greenhouse to icehouse: a biostratigraphic review of latest Devonian–Mississippian glaciations and their global effects

Abstract: The latest Devonian to Mississippian interval records the long term transition from 12Devonian Greenhouse conditions into the Late Palaeozoic Ice Age (LPIA). This transition was 13 punctuated by three short glaciation events in the latest Famennian, mid Tournaisian and Viséan 14 stages respectively. Primary evidence for glaciation is based on diamictite deposits and striated 15 pavements in South America, Appalachia and Africa. The aim of this review is to assess the primary 16 biostratigraphical and sedimento… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 99 publications
2
47
0
Order By: Relevance
“…But the latest Famennian Stensiö Bjerg Formation had greater seasonality with wetter wet times and drier dry times as shown by the presence of lakes and calcretes rather than a stack of vertisols. This can be attributed to the latest Famennian glaciations (as reviewed in Lakin et al 2016) that in the Borders showed the cumulative far-field response of a composited supermature calcrete representing a significant arid hiatus in excess of several hundred thousand years per calcrete horizon (Wright et al 1993). Hence the top of the Kinnesswood Formation at Pease Bay is placed at the top of the range of Remigolepis to reflect a view that the most likely condensed interval would be the latest Famennian glacial cycles.…”
Section: Pease Baymentioning
confidence: 99%
“…But the latest Famennian Stensiö Bjerg Formation had greater seasonality with wetter wet times and drier dry times as shown by the presence of lakes and calcretes rather than a stack of vertisols. This can be attributed to the latest Famennian glaciations (as reviewed in Lakin et al 2016) that in the Borders showed the cumulative far-field response of a composited supermature calcrete representing a significant arid hiatus in excess of several hundred thousand years per calcrete horizon (Wright et al 1993). Hence the top of the Kinnesswood Formation at Pease Bay is placed at the top of the range of Remigolepis to reflect a view that the most likely condensed interval would be the latest Famennian glacial cycles.…”
Section: Pease Baymentioning
confidence: 99%
“…Increased weathering rates related to global cooling events have been recorded as having coincided with the expansion of Cenozoic ice sheets during the Eocene-Oligocene transition and Early-Mid Pliocene (e.g., Blum, 1997;Robert and Kennett, 1997;von Blanckenburg and O'Nions, 1999), as well as throughout the formation of alpine-style glaciers in the Alpine-Himalayan belt (Herman et al, 2013). Additionally, continental weathering pulses have been associated with the onset and termination of both the Late Ordovician and Fammenian glaciations, which also occurred broadly coevally with the development of widespread marine anoxia/euxinia and major faunal extinctions (e.g., Finlay et al, 2010;Kaiser et al, 2016;Lakin et al, 2016). However, whilst it is clearly possible to trigger enhanced continental weathering and/or marine anoxia during times of cooling and glacial expansion, conclusively demonstrating such a model for the Kellwasser events is inhibited by the lack of clarity regarding the precise temporal relationship between the two crises and the onset of global cooling associated with each of them.…”
Section: Possible Causes Of the Frasnian-famennian Weathering Pulsesmentioning
confidence: 99%
“…Higher resolution temperature and weathering proxy data are needed to clarify whether the Kellwasser cooling occurred in response to elevated silicate weathering and organic-carbon burial during the two crises, or could have initiated those environmental perturbations. An additional problem with the hypothesis of glacially-induced-weathering is that although both a southern-hemisphere ice sheet and additional alpine-style glaciers of latest Famennian age are well documented by diamictite deposits in numerous South American sedimentary basins and the North American Appalachian Basin (e.g., Caputo et al, 1985;Brezinski et al, 2008;Isaacson et al, 2008;Lakin et al, 2016), similar sediments spanning the Frasnian-Famennian boundary are unknown.…”
Section: Possible Causes Of the Frasnian-famennian Weathering Pulsesmentioning
confidence: 99%
See 1 more Smart Citation
“…A list of knowledge gaps and research directions shows how far we still are from a full understanding of this undoubted first-order mass extinction and global ecosystem overturn. Lakin et al (2016) review the precise ages of uppermost FamennianVisean glacial deposits, especially of South America, and provide evidence for three 'precursor glaciations' before the onset of long-term (Upper Carboniferous -Permian) icehouse climates. They stress the current uncertainties of the mostly palynomorph-based dating, especially for the onset of glaciations, when still few diamictites were formed.…”
mentioning
confidence: 99%